SEDIMENTOLOGY, STRATIGRAPHY AND DIAGENETIC HISTORY OF BUKIT CHONDONG-BUKIT TUNKU LEMBUBUKIT CHUPING, PERLIS - AZALAN, SITI AISHAH (Universiti Teknologi PETRONAS, 2015)
The Permian age Uppermost Kubang Pasu Formation was found underlying the Chuping Formation in the North Peninsular of Malaysia. An integrated study comprising sedimentology, stratigraphy of the Uppermost Kubang Pasu and diagenetic history of Chuping Limestone has been conducted by involve three research location which is Bukit Chondong, Bukit Tungku Lembu and Bukit Chuping, Perlis. The purposes of this research are to construct the stratigraphy log as a result to correlate the respective logs, to identify the lithofacies, to recognize the depositional environment and to determine the source rock potential of the Uppermost Kubang Pasu Formation in Bukit Chondong and Bukit Tungku Lembu, Beseri Perlis. The details analysis of diagenetic history on the Chuping Limestone was carried out in Bukit Chuping, Kangar, Perlis. Two lithostratigraphy logs and cross section have been generated for the research area, one from Bukit Chondong and one from Bukit Tungku Lembu which composed of the Uppermost Kubang Pasu Formation. The clastic rocks samples have been taken from Bukit Chondong and Bukit Tungku Lembu while the carbonate rocks sample are taken from Bukit Chuping for several laboratory analysis such as thin section, X-Ray Diffraction and Total Organic Carbon. The uppermost Kubang Pasu Formation has been identified as coarsening upward facies distribution pattern throughout the study area. The lithofacies has been identified in four facies which are (i) massive sandstone (F1), (ii) parallel lamination sandstone (F2), (iii) tabular cross lamination sandstone (F3) and (iv) mudstone (F4). These facies are grouped into three facies association namely FA1- offshore to transitional zone, FA2-distal shoreface and FA3- proximal shoreface. Trace fossils analysis showed that offshore to shoreface water environment were in this study area. The shoreface fossils are crinoids and brachiopods. Based on the petrographic analysis, the sandstone is mostly quartz arenite with a few subarkose. The total organic content has found there is a potential source rock, thus this correspond to the environment of deposition which sediment deposits in anoxic environment with dissolved oxygen concentration of less than .5 milligrams per litre.